La cromoterapia y su incidencia en el comportamiento de los niños y niñas de primer año de educación básica de la Unidad Educativa “José Alejo Palacios” de la ciudad de Loja. Periodo Lectivo 2013-2014”. Lineamientos alternativos - Criollo Suárez, Nancy Gabriela (2015)
This research entitled "CHROMOTHERAPY AND ITS IMPACT ON THE BASIC EDUCATION FIRST YEAR CHILDREN BEHAVIOR" JOSE PALACIOS ALEJO SCHOOL" LOJA CITY. ACADEMIC YEAR 2013-2014 ". ALTERNATIVE GUIDELINES, it is structured according to the current Rules of Academic System at the National University of Loja. The general objective that guided the research process was: To determine the incidence of Chromotherapy in the Basic Education First Year Children Behavior" Jose Palacios Alejo School "Loja City The methods used were: Scientist, Inductive-Deductive, Analytic-Synthetic, Descriptive and Statistical Model. The techniques used were: Survey applied teachers of Basic Education First Year Children "Alejo José Palacios school" to establish the level of knowledge of the Cromoterapy they have; and, The Observation Guide applied to children education Educational Unit "Alejo José Palacios" city of Loja, to identify the types of behavior they exhibit. In implementing the survey found that teachers: 100% of teachers surveyed report that the concept of Chromotherapy is a form of psychotherapy, related to art, which is based on the therapeutic use of colors. : 100% of teachers surveyed respond that uses chromotherapy are so that people can be cured of diseases so that children have different behavioral manifestations, and to prevent the occurrence of impairments (biological, psychological and social) . According to the results of the observation guide, the following result was obtained: 54% of children have investigated Shy Behaviors and 46% no; 38% have Assertive Behaviors and 62% no; 16% have liabilities behaviors and 84% no; and 11% have Aggressive Behaviors and 89% no..